Embracing Complexity Within Creative Approaches to Dementia Research: Ethics, Reflexivity, and Research Practices - Campbell, Sarah (Int J Qual Methods, 2023)
In this paper, we present reflections from three research studies that have engaged with creative approaches to qualitative research with people living with dementia. Creative approaches to qualitative research are increasingly advocated within dementia research as they foreground alternative routes to expression and can facilitate flexible, meaningful participation. Such approaches are typically cited as illuminating people’s lived experiences as they often enable nuanced understandings around how people with dementia engage in the world around them. Yet creative approaches to research with people living with dementia involve specific complexities that require rigorous planning, generous timelines, and interdisciplinary research teams. It is important to examine the role of the researcher(s) in the development and application of creative approaches, as this impacts the extent to which the voices and experiences of people living with dementia are authentically heard and felt throughout the research. In this reflective article, we come together as three researchers who have used a range of creative and sensory approaches to understand the everyday lived experiences of people living with dementia in different contexts. We present examples taken from three doctoral research studies in which we navigated the creative research space to ensure the voices of people living with dementia are placed centrally and actively within the research process. We pay particular attention to the creative reflexive processes used in each example and explore what ethical research practices look and feel like in the context of creative research with people living with dementia. Our critical reflections lead us to discuss the opportunities that embracing creative approaches may afford in future research with people living with dementia.